MENILAI KINERJA KEUANGAN UNTUK MENGUKUR KESEHATAN KOPERASI KARYAWAN (KOPKAR) MAJELIS LUHUR PERSATUAN TAMANSISWA “SEJAHTERA” DI YOGYAKARTA - Salsa Bella Larasati (Journal Of Business, Finance, and Economics (JBFE), 2020)
This research was conducted to determine the financial performance of the Employee Cooperative (KOPKAR) Majelis Luhur Persatuan Tamansiswa "SEJAHTERA" with reference to the decision of the Minister of Cooperatives and Small and Medium Enterprises No. 06 / Per / Dep.6 / IV / 2016 regarding guidelines for health assessment of savings and loan cooperatives and cooperative savings and loan units. This research is descriptive quantitative, the data source used is secondary data with the time series method which comes from the financial statements of the balance sheet and the income statement between 2014 and 2018. The data analysis technique in this study uses quantitative analysis, namely using the ratio as a measuring tool, The ratios used in this study are the ratio of capital, quality of productive assets, management, efficiency, liquidity, independence and growth, cooperative identity.